Regional Dialect VS Islamic Boarding Students: Their Relationship in Improving Speaking Ability - Nurhidayah, Yayah; Syukur, Hasan; Rashid, Ungaran (Papanda Publisher, 2024)
Geoghraphical conditions had an influence through the dialect, vocabulary and syntax used by people. Islamic Boarding School was a place where people go to looking for knowledge whose come from come from different palace and region. This reseach purposed to analyze the students' Regional Dialect; its influence and its correlation toward students speaking achievement. The subjects of this study were students of Islamic Boarding of Santi Asromo which located in West Java – Indonesia.In obtaining an actual data, the researcher used descriptive qualitative method. Observation, Interview and Documentation were used as instruments. After data have been analyzed, the result showed that the speaking ability of Santi Asromo Islamic Boarding students were influenced by their own Regional Dialect. It can be said that regional dialects have a correlation with the students’ speaking achievement. In the last, this study suggests that the English teacher/ dormitory principle should provide a workbook and suitable strategy to finalize the regional dialect influence faced by students in learning Speaking. Keywords: Regional Dialect, Islamic Boarding and Speaking Ability,